2007
DOI: 10.1111/j.1365-2966.2007.00399.x
|View full text |Cite
|
Sign up to set email alerts
|

Canadian cities as regional engines of growth: agglomeration and amenities

Abstract: Abstract.  Canadian regional population growth is less understood than that of the United States. In both countries, certain regions have persistent population growth. Yet, unlike U.S. trends of amenity‐driven migration away from historic urban centres, Canadian growth is more urban centric. This study assesses whether agglomeration economies in the few major Canadian metropolitan areas lead to population growth in or near these cities rather than the more‐dispersed U.S. patterns. The results suggest that disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 48 publications
1
51
0
1
Order By: Relevance
“…They also find that small rural communities need to improve factors determining quality of life to be able to benefit from urban spillovers. In a related paper, Partridge et al (2007b) show that large Canadian cities are engines for growth. In a more recent paper Lavesson (2017) finds that rural to urban commuting in Sweden has a positive effect on rural employment.…”
Section: %mentioning
confidence: 97%
“…They also find that small rural communities need to improve factors determining quality of life to be able to benefit from urban spillovers. In a related paper, Partridge et al (2007b) show that large Canadian cities are engines for growth. In a more recent paper Lavesson (2017) finds that rural to urban commuting in Sweden has a positive effect on rural employment.…”
Section: %mentioning
confidence: 97%
“…Recent studies have indicated that the region is more vulnerable to climate change than any other part of Canada (Deng et al, 2016;Mailhot et al, 2012). Furthermore, Southern Ontario is one of the prominent economic hubs, with the largest population concentration in Canada (Bourne and Simmons, 2003;Kerr, 1965;Partridge et al, 2007). In this context, we explore a robust statistical framework to evaluate possible nonstationary trends, analyse the frequency of urban precipitation extremes, and assess the risk of severe rain-induced urban flooding in Southern Ontario (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…However, this role seems to vary somewhat between countries and by age of worker. For instance, amenities appear to have a stronger effect in the United States (Partridge and Rickman, 2003) than in Canada (Ferguson et al, 2007; Partridge et al, 2007). As well, amenities are more important in the location decisions of young people (Ferguson et al, 2007) and workers nearing retirement (Ferguson et al, 2007; Scott, 2010).…”
Section: Introductionmentioning
confidence: 99%